Revision of the Afrotropical species of the Bengalia peuhi species-group, including a species reassigned to the B. spinifemorata species-group (Diptera, Calliphoridae), with notes on the identity of Ochromyia petersiana Loew, 1852 (Diptera, Rhiniidae) - Rognes, Knut (Zootaxa, 2012)
Eleven Afrotropical species of Bengalia Robineau-Desvoidy, ten in the Bengalia peuhi species-group and one reassignedto the Bengalia spinifemorata species-group, are revised. The male genitalia of all, and the ovipositor of six species, areillustrated by means of digital colour photography. A key to males is provided. Two species, i.e., Bengalia minor Malloch,1927 and Bengalia peuhi Villeneuve, 1914, are assigned to the Bengalia peuhi subgroup of the Bengalia peuhi species-group. Five species, i.e., Bengalia depressa Walker, 1858, Bengalia floccosa Wulp, 1885, Bengalia gaillardi Surcouf &Guyon, 1912, Bengalia roubaudi Rickenbach, Hamon & Mouchet, 1960 and Bengalia tibiaria Villeneuve, 1926 areassigned to the Bengalia floccosa subgroup of the Bengalia peuhi species-group. Three species, i.e., Bengalia africanoidessp. nov., Bengalia aliena Malloch, 1927 and Bengalia wyatti (Lehrer, 2005) comb. nov., have been left as species incertaesedis in the Bengalia peuhi species-group. The eleventh species, Bengalia bantuphalla (Lehrer, 2005) comb. nov., is re-assigned to the Bengalia spinifemorata species-group. Bengalia africanoides sp. nov. has only 3 post dc setae, a featureunique for a species of Bengalia. A neotype is designated for Calliphora floccosa Wulp, 1885 (now in Bengalia), to fixthe interpretation of the name in accordance with current usage. Lectotypes are designated for Bengalia bekilyana Séguy,1935, Bengalia depressa, Bengalia gaillardi, Bengalia peuhi and Bengalia unicalcarata Villeneuve, 1913 to fix theinterpretation of the names. Bengalia africana Malloch, 1927 is established as a junior synonym of Bengalia depressa,syn. nov. Bengalia cuthbertsoni Zumpt, 1956 is established as a junior synonym of Bengalia tibiaria, syn. nov.Shakaniella sakinehae Lehrer, 2011 is established as a junior synonym of Shakaniella wyatti (now in Bengalia), syn. nov.Tsunamia yourubana Lehrer, 2005 is established as a junior synonym of Bengalia aliena, syn. nov. Ochromyia petersianaLoew, 1852 is removed from its current position as a doubtful senior synonym of Bengalia depressa and transferred to thegenus Thoracites Brauer & Bergenstamm, 1891 as Thoracites petersiana, comb. nov. in the Rhiniidae. This name is proposed as a senior synonym of Thoracites neglectus Zumpt, 1972, syn. nov.